Narrativas de padres con hijos en edad escolar sobre las competencias parentales durante el confinamiento social debido al COVID-19 (2021)
The present qualitative research aims to analyze the narratives used by four mothers interviewed with school-age children between 6 and 11 years of age about the use of parental skills during social confinement due to the virus or disease COVID-19. To obtain better results in the research, it was considered pertinent to use a narrative design of topics, using as an instrument an in-depth interview used in the four mothers. As an important finding, it is identified that the circumstances of confinement affect the development of parental competences, achieving the strengthening of some of them. On the other hand, family dynamics are affected by the appearance of new risks that arise as a result of confinement and the COVID-19 virus, which parents have to face through the use of new resources through parental skills. with a progressive adaptation